GETTING BY WITH A LITTLE HELP FROM MY FRIENDS: FUNCTIONAL LIMITATIONS AND DAILY EMOTIONAL EXPERIENCES. (11th November 2018) - Charles, S; Hong, J H; Leger, K A; Fingerman, K
Abstract: Social networks play important roles in the lives of people with functional limitations. Yet, social networks are comprised of different relationships (e.g., child, friend) that serve different needs. The current study examined how interactions with different social members were related to emotional experiences in adults with and without functional limitations. Older adults (N=313) from the Daily Experiences and Well-being Study reported their social interactions (e.g., being alone or interacting with different social partners) and emotional experiences (positive and negative affect) every three hours across approximately 5 days. People with limitations reported lower positive affect than people without limitations, but differences were greatest when people were alone. Both groups reported higher positive affect with friends, but people with limitations benefited more than those without limitations. This pattern was not the same for negative affect or other types of relationships. Overall, results indicate the importance of friendships when understanding health and well-being.